Association of Simulation-Based Team Training Implementation with Treatment Process Optimization and Clinical Outcomes in a Chest Pain Center: A Retrospective Pre-Post Analysis of Real-World Data. - Liu, Sha; Wang, Pengyu; Song, Shaohua; Zhang, Fan; Chen, Ying; Liu, Pujuan; Jiang, Xinyan (Journal of Multidisciplinary Healthcare, 2026)
Background: Efficient multidisciplinary teams in chest pain centers are critical for ST-segment elevation myocardial infarction (STEMI) outcomes. Simulation-based team training (SBTT) may enhance team performance, but real-world clinical impacts remain under-documented. This study evaluated the association between a systematic SBTT program and treatment processes and clinical outcomes in STEMI patients. Methods: We conducted a retrospective pre-post analysis at a tertiary center in China. Consecutive STEMI patients undergoing primary percutaneous coronary intervention (May 2020–June 2023) were included. Patients were divided into pre-intervention (May 2020–Dec 2021) and post-intervention (Jan 2022–June 2023) groups, separated by the implementation of a multidisciplinary SBTT program. Primary outcomes were door-to-balloon (D2B) and first-medical-contact-to-balloon (FMC-to-B) times. Interrupted time series (ITS) analysis assessed D2B time changes. Results: We included 260 patients (125 pre-intervention, 135 post-intervention). Post-SBTT, median D2B time decreased from 92 to 68 minutes (p < 0.001), and FMC-to-B time from 125 to 95 minutes (p < 0.001). Patients achieving D2B ≤ 90 min increased from 44.8% to 85.2% (p < 0.001). ITS analysis showed an immediate D2B time drop of 23.5 minutes (p < 0.001). In-hospital MACE rates decreased from 12.8% to 5.2% (p = 0.031). Conclusion: These findings suggest that SBTT could be a valuable quality improvement tool in chest pain centers for optimizing the timeliness of reperfusion therapy and clinical outcomes. However, further prospective, multicenter studies are needed to confirm these findings and establish definitive causality before universal adoption can be firmly recommended.